Analysis of the integration of the hot-lab method in resistor practical work using incandescent lamps on the topic of conductor resistance with PhET virtual lab - Mulhayatiah, Diah; Rachman, Muhammad Ziddan; Malik, Adam; Agustina, Rena Denya; Chusni, Muhammad Minan; Yuningsih, Endah Kurnia (Education and Development Research, 2025)
In the digital era, students still face difficulties in understanding abstract physics concepts such as Ohm's Law and resistance, primarily due to conventional, teacher-centered instructional methods. This study aims to investigate the integration of the Higher-Order Thinking Laboratory (HOT-Lab) method with PhET virtual simulations to improve students’ higher-order thinking skills (HOTS) in learning about conductor resistance. Using an experimental method, students conducted virtual practicum activities via the PhET Interactive Simulations platform, specifically utilizing the